(untitled) (Research, Society and Development, 2019)
This paper presents the analysis of seven essays that received maximum score in the National Examination of High School in accordance with Systemic Functional Linguistics, proposed by Halliday (1982), Martin e Rose (2008) e Rose e Martin (2012). The purpose of the study was to verify the lexical-grammatical elements used in the argumentative proposal of the 1000 graded essays in the year 2014, with the aim of describing the genre. The research is characterized by being a documentary analysis based on semantic-discursive analysis of the seven selected texts for research. This analysis helps in understand about the linguistic resources used for the student to convince the examining board about the proposal and how these resources produces texts from the Arguments family. The analyzed samples presented typical stages of the Exposition and Discussion genres, according the Sydney School, demonstrating that the context of the test requires the students to present other points of view besides arguments that support their opinion.